The Concept of Rûh in Islam: An Interdisciplinary Analysis of Interpretation, Philosophy, and Theology - Ad-Diba'i, Muhammad Daffa Syafiq Nashr (Centre for Literary and Cultural Studies, 2025)
The concept of Rûh constitutes a central theme in Islamic anthropology that has sparked intensive debate among Quranic exegetes, Muslim philosophers, and theologians from the classical to contemporary era. The semantic diversity of Rûh in the Qur'an : as the animating force of the body, the angel Jibrîl, revelation, and divine assistance, poses complexity in formulating a comprehensive definition. This study aims to construct a comprehensive definition of Rûh through an interdisciplinary approach that integrates Quranic exegesis, Islamic philosophy, and theology by employing Islamic epistemology (bayânî, burhânî, ‘irfânî) as an analytical framework. The research method employed is qualitative with a library research design that applies content analysis, comparative analysis, hermeneutics, and interdisciplinary synthesis to primary sources (the Qur'an, classical-contemporary tafsîr, works of Muslim philosophers) and secondary sources (scholarly journals from the last 10 years). The research findings demonstrate that Rûh is an immaterial substance that is hadîth (created) originating from God's command (min amri Rabbî), functioning as the animating force of the body and source of life, connecting humans with the divine dimension, and possessing figurative eternal nature (not perishing with bodily death). Despite terminological variations, a fundamental consensus indicates that Rûh is an independent non-material substance, distinct from nafs (soul) in function and characteristics. Comprehensive understanding of Rûh has significant implications for 'aqîdah (belief in resurrection and afterlife) and adab (spiritual ethics through tazkiyah al-nafs, intellectual humility, and reverence for life).